Menangani stres pada anak dari keluarga broken home: MENANGANI STRES PADA ANAK DARI KELUARGA BROKEN HOME - Rahmania, Chafidhotur (Maliki Interdisciplinary Journal, 2025)
Stress in children from broken homes is a serious concern in the fields of psychology and education. Children in this situation often experience complex emotional challenges, hindering their holistic development. Peer counseling offers a promising approach to dealing with this stress. This research explores the effectiveness of peer counseling in reducing stress in these children. Using qualitative experimental methods, the research results show that peer counseling is effective in reducing stress and improving children’s well-being. In-depth analysis revealed feelings of support and connection among participants, as well as improvements in emotion and conflict management skills. The implications of these findings are particularly relevant in the context of education and child welfare, suggesting that peer counseling can be an important strategy in helping children deal with the emotional impact of parental divorce or separation.